General Prıncıples And Vısual Presentatıon In The Reports Of Orthodontıcaly Treated Cases - M. Serdar Toroğlu (Galenos Yayinevi, 1998)
To be effective in visual presentations, many details have to be considered. Topic of the meeting, audience, meeting hall, and technical support etc.. The preparation of visual presentation should be started after this detailed examination. In visual presentations, most distinctive mistakes are; discommunication with audience and being not able make standarts during the same presentation or with the other presentations. As also audience have some resposibilities to the person who makes his/her visual presentation.